WEBSITE DESIGN AND CONSTRUCTION SINGLE-PAGE AS A PROMOTIONAL MEDIA AT TBS (TATA BEAUTY SALON) WONOAYU DISTRICT, SIDOARJO - Ahmad Ardiansyah Nugraha; Hindarto Hindarto; Ade Eviyanti; Novia Ariyanti (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to design and implement a website-based digital marketing system as an effective promotional strategy for Tata Beauty Salon (TBS) in Wonoayu District, Sidoarjo. Background: Currently, TBS relies solely on direct interaction and word-of-mouth marketing, which limits the dissemination of information and hinders business growth and competitiveness. Method: The research applies the Waterfall model of the Software Development Life Cycle (SDLC) to develop a single-page website that presents all essential information—such as services, pricing, and contact details—on one interface for a seamless user experience. The website is built using HTML and CSS for layout and design, while PHP and JavaScript are used for functional programming. Results: The implementation of the website enhances TBS’s online visibility, simplifies customer access to information, and improves promotional reach. Novelty: This research demonstrates how a simple, user-friendly single-page website can serve as an effective digital marketing tool for small businesses, contributing to increased competitiveness and sustainable business growth in the beauty industry.